Obtaining by coprecipitation method complex oxide compounds with the garnet structure with stoichiometric and nonstoichiometric composition for the LEDs emitting white color - Bokshyts, Yuliya V.; Korjik, Mikhail V.; Tratsiak, Yauhen V.; Shevchenko, Gvidona P. (Journal of the Belarusian State University. Chemistry, 2017)
New compounds with garnet structure, activated by cerium, with stoichiometric and non-stoichiometric composition were synthesized by using of colloid-chemical approach. The possibility of using homo- and heterovalent substitution of Y3+ and Al3+ in garnet structure and introduction of the substituent cations in a form of hydrosols of their oxides for tuning of spectral-luminescence properties of the garnets was shown. Developed Y1.5La1.5Al2(AlO4)3 : Ce and Y2MgAlGe(AlO4)3 : Ce phosphors may be perspective for using in a power efficient light sources with improved color characteristics.